Genomic Diversity of Listeria monocytogenes Isolates From Slovakia (2010 to 2020) - Kubicová, Zuzana; Roussel, Sophie; Félix, Benjamin; Cabanová, Lenka (Frontiers in Microbiology, 2021)
Over the past 11 years, the Slovak National Reference Laboratory has collected a panel of 988 Listeria monocytogenes isolates in Slovakia, which were isolated from various food sectors (61%), food-processing environments (13.7%), animals with listeriosis symptoms (21.2%) and human cases (4.1%). We serotyped these isolates by agglutination method, which revealed the highest prevalence (61.1%) of serotype 1/2a and the lowest (4.7%) of serotype 1/2c, although these represented the majority of isolates from the meat sector. The distribution of clonal complexes (CCs) analysed on 176 isolates demonstrated that CC11-ST451 (15.3%) was the most prevalent CC, particularly in food (14.8%) and animal isolates (17.5%). CC11-ST451, followed by CC7, CC14 and CC37, were the most prevalent CCs in the milk sector, and CC9 and CC8 in the meat sector. CC11-ST451 is probably widely distributed in Slovakia, mainly in the milk and dairy product sectors, posing a possible threat to public health. Potential persistence indication of CC9 was observed in one meat facility between 2014-2018, highlighting its general meat-related distribution and potential for persistence worldwide.